Indigenous Materials as Catalyst Supports for Renewable Diesel Production in Malaysia - Chia S.R.; Nomanbhay S.; Chew K.W.; Show P.L.; Milano J.; Shamsuddin A.H. (MDPI, 2023)
Biodiesel; Catalyst selectivity; Catalyst supports; Diesel engines; Fuel storage; Potential energy; Catalysts support; Catalytic properties; Diesel production; Energy demands; Enhancement; Indigenous materials; Malaysia; Recyclability; Renewable diesels; ]+ catalyst; Zeolites